Timing of Mesenchymal Stromal Cell Therapy Defines its Immunosuppressive Effects in a Rat Lung Transplantation Model - Yukinori Tanoue; Tomoshi Tsuchiya; Takuro Miyazaki; Mayumi Iwatake; Hironosuke Watanabe; Hiroshi Yukawa; Kazuhide Sato; Go Hatachi; Koichiro Shimoyama; Keitaro Matsumoto; Ryoichiro Doi; Koichi Tomoshige; et al. (Cell Transplantation, 2023)
Cell therapy using mesenchymal stromal cells (MSCs) is being studied for its immunosuppressive effects. In organ transplantation, the amount of MSCs that accumulate in transplanted organs and other organs may differ depending on administration timing, which may impact their immunosuppressive effects. In vitro , adipose-derived mesenchymal stem cells (ADMSCs) suppress lymphocyte activation under cell-to-cell contact conditions. However, in vivo , it is controversial whether ADMSCs are more effective in accumulating in transplanted organs or in secondary lymphoid organs. Herein, we aimed to investigate whether the timing of ADMSC administration affects its immunosuppression ability in a rat lung transplantation model. In the transplantation study, rats were intramuscularly administered half the usual dose of tacrolimus (0.5 mg/kg) every 24 h after lung transplantation. ADMSCs (1 × 10 6 ) were administered via the jugular vein before (PreTx) or after (PostTx) transplantation. Cell tracking using quantum dots was performed. ADMSCs accumulated predominantly in the lung and liver; fewer ADMSCs were distributed in the grafted lung in the PreTx group than in the PostTx group. The rejection rate was remarkably low in the ADMSC-administered groups, particularly in the PostTx group. Serum tumor necrosis factor-α (TNF-α), interferon-γ, and interleukin (IL)-6 levels showed a greater tendency to decrease in the PreTx group than in the PostTx group. The proportion of regulatory T cells in the grafted lung 10 days after transplantation was higher in the PostTx group than in the PreTx group. PostTx administration suppresses rejection better than PreTx administration, possibly due to regulatory T cell induction by ADMSCs accumulated in the transplanted lungs, suggesting a mechanism different from that in heart or kidney transplantation that PreTx administration is more effective than PostTx administration. These results could help establish cell therapy using MSCs in lung transplantation.